Physical interaction with Spo11 mediates the localisation of Mre11 to chromatin in meiosis and promotes its nuclease activity - Aithal, Rakesh; Nangalia, Kuldeep; Spirek, Mario; Chen, Doris; Klein, Franz; Krejci, Lumir (Nucleic acids research, 2024)
Meiotic recombination is of central importance for the proper segregation of homologous chromosomes, but also for creating genetic diversity. It is initiated by the formation of double-strand breaks (DSBs) in DNA catalysed by evolutionarily conserved Spo11, together with additional protein partners. Difficulties in purifying the Spo11 protein have limited the characterization of its biochemical properties and of its interactions with other DSB proteins. In this study, we have purified fragments of Spo11 and show for the first time that Spo11 can physically interact with Mre11 and modulates its DNA binding, bridging, and nuclease activities. The interaction of Mre11 with Spo11 requires its far C-terminal region, which is in line with the severe meiotic phenotypes of various mre11 mutations located at the C-terminus. Moreover, calibrated ChIP for Mre11 shows that Spo11 promotes Mre11 recruitment to chromatin, independent of DSB formation. A mutant deficient in Spo11 interaction severely reduces the association of Mre11 with meiotic chromatin. Consistent with the reduction of Mre11 foci in this mutant, it strongly impedes DSB formation, leading to spore death. Our data provide evidence that physical interaction between Spo11 and Mre11, together with end-bridging, promote normal recruitment of Mre11 to hotspots and DSB formation.
Keywords: Protein Binding; Saccharomyces cerevisiae Proteins; Exodeoxyribonucleases; endodeoxyribonukleasy; mutace; exodeoxyribonukleasy; Saccharomyces cerevisiae; Meiosis; DNA vazebné proteiny; dvouřetězcové zlomy DNA; DNA Breaks, Double-Stranded; chromatin; Chromatin; vazba proteinů; meióza; Endodeoxyribonucleases; Saccharomyces cerevisiae - proteiny; Mutation; DNA-Binding Proteins